The Growth mentality to achieve goals and a happy life - Alves, Felipe Freitas de Araújo (2024)
In this paper we will talk about growth mindset, fixed mindset and happiness and their main notions. We know that a growth mindset can help people achieve their goals, both personal and professional, and as a result, achieve a happier and fuller life. In this context we will see what mindsets are about, both fixed and growth, and why changing the mindset from fixed to growth will bring real possibilities to help on the path to the achievements already mentioned above. Theobjective of this work is to highlight the growth mindset to achieve goals and a happy life. This workwas based on a bibliographical research consulting books, magazines and scientific articles on theproposed topic.